Problematika Paradigma Pendidikan Mts Darut Tauhid Ngablak Bojonegoro - HENDRA SETIAWAN; Minarti, Sri (At-Tuhfah : Jurnal Studi Keislaman, 2024)
Secularism is an ideology that only prioritizes material things and separates worldly life from the afterlife. In fact, this ideology always fights for the right to be free from various rules from religious teachings. there may be a role and interference of religion in it. The concept of secularism has been spreading for a long time in Indonesia. The influence of secularism on the Islamic world began during the era of western imperialism on the Islamic world. The methodology used in this research is qualitative using a historical approach through library research which utilizes sources from various journals and several books that are appropriate to the research topic. The results of this research show that secularism is a view that is contrary to teachings Islam separates world affairs from religious affairs. Sadly, there are quite a few Muslims who adhere to secularism, they act freely in dealing with world affairs and religion, reject Islamic law, and do not even believe in the Alqur’an and religion as true guidelines for life. Of course this is a big challenge in Islamic preaching. This requires serious attention and handling from Islamic figures, ulama and Muslims themselves.